(untitled) (Research, Society and Development, 2021)
According to the World Health Organization, a new adverse health condition affects and spreads pandemicly in different continents with sustained transmission from person to person, namely SARS-CoV-2. The aim of this study is to analyze the perception of Spinning practitioners in participating in remote classes during the COVID-19 pandemic isolation period. This study is an experience report as a remote Spinning class instructor, carried out in the first half of 2020, where a form from the Google Forms platform was applied with the participation of 30 individuals, with questions about the experience of performing remote training Spinning. Among the results found, it was observed that all participants were female, that 68.2% of users reported that the experience of exercising at home was excellent; most users attended classes 2 or 3 times a week; regarding the use of the digital platform during virtual classes, most judged the tool to be excellent. Given the assumption, it can be concluded that the experience of participating in remote Spinninig classes at home, at the time of social isolation imposed by COVID-19, was very beneficial to the physical and emotional health of practitioners, and that actions such as these should be encouraged and stimulated, given the importance of staying active and taking care of our health even in periods of pandemic and social isolation.